MEDICINAL PLANT SPECIES IDENTIFICATION SYSTEM USING TEXTURE ANALYSIS AND MEDIAN FILTER - Prihastuti Harsani; Arie Qurania; Triasti nurmiatiningsih (Jurnal Ilmiah Kursor, 2016)
Identification of plants can be done through objects - objects in plants by asking an expert or through a specimen (herbarium) that have been identified previously. Identification is done by matching the pictures in the book of flora or monograph. Computer-aided identification can be done using digital image processing methods which utilize digital image matching object plant with a picture on the book. Identification key that is used is the image of the leaves. This study develops previous research has identified using the method of fractal and Euclidian Distance. Accuracy obtained in each of the identification system for the fractal dimension and fractal code is of 68% and 51%. Improved accuracy is the main objective of this study. The proposed method is a method of texture analysis and median filter. Texture analysis is used as feature extraction technique while the median filter is image enhancement techniques. Based on the trials, the results of the identification of texture analysis method and median filter to increase to 78%. Median filter is used as a technique to improve the image quality leaves. The use of an identification system to be tested in the web application of information systems of medicinal plants.